From Traditional Work to Hybrid Work: A Narrative Review of Evolution, Antecedents, Dimensions, Outcomes, and Scholarly Debates - Kumar, Manoj; Akmal, Suriati; Luqman, Razi; Hussain, Zainab (Journal of Human Capital Development (JHCD), 2025)
The nature of work has undergone profound transformation over the past century, driven by technological advancements, economic restructuring, and shifting societal expectations. Most recently, the COVID-19 pandemic accelerated a global transition toward flexible work arrangements, culminating in the widespread adoption of hybrid work environments that combine on-site and remote work. This narrative review synthesizes interdisciplinary scholarship to examine the historical evolution of work from traditional, location-bound models to telework, remote work, and contemporary hybrid configurations. Drawing on organizational, sociological, and psychological literatures, the review explores the emergence of hybrid work as a response to technological enablement, organizational needs, and employee expectations. The paper further analyzes the key dimensions of hybrid work, its antecedents at individual, organizational, and societal levels, and its outcomes for employees, teams, and organizations. Particular attention is given to ongoing scholarly debates regarding the benefits and drawbacks of hybrid work, including productivity, well-being, equity, and organizational control. The review also integrates major theoretical perspectives—such as sociotechnical systems theory, job demands–resources theory, and boundary theory—to explain how hybrid work reshapes contemporary employment relationships. By consolidating fragmented research across disciplines, this review contributes a comprehensive conceptual foundation for understanding hybrid work environments and identifies critical gaps to guide future research and evidence-based organizational practice.